Current state of knowledge of post-traumatic stress, sleeping problems, obesity and cardiovascular disease in paramedics. Issue 3 (12th January 2013) - Hegg-Deloye, Sandrine; Brassard, Patrice; Jauvin, Nathalie; Prairie, Jérôme; Larouche, Dominique; Poirier, Paul; Tremblay, Angelo; Corbeil, Philippe
Abstract : Purpose: The impacts of emergency work on firefighters have been well documented and summarised, but this is not the case for paramedics. This paper explores the literature regarding the impact of work stress on paramedics. Objective: To identify the literature available on the effect of paramedics' jobs on their health status. Methods: Electronic database used: MEDLINE (Ovid, PubMed, National Library of Medicine) between 2000 and 2011. Key words used for the computer searches were: paramedics, emergency responders, emergency workers, shift workers, post-traumatic symptoms, obesity, stress, heart rate variability, physiological response, blood pressure, cardiovascular and cortisol. Exclusion criteria were: studies in which participants were not paramedics, participants without occupational exposure, physical fitness assessment in paramedics and epidemiological reports regarding death at work. Results: The electronic databases cited 42 articles, of which we excluded 17; thus, 25 articles are included in this review. It seems clear that paramedics accumulate a set of risk factors, including acute and chronic stress, which may lead to development of cardiovascular diseases. Post-traumatic disorders, sleeping disorders and obesity are prevalent among emergency workers. Moreover, their employers use no inquiry or control methods to monitor their health status and cardiorespiratory fitness. Conclusions: More studies are needed to characterise paramedics' behaviour at work. These studies could allow the development of targeted strategies to prevent health problems reported in paramedics.